Atividades urbanas : um parâmetro de planejamento urbano para o desenvolvimento de cidades brasileiras - Ghesla, Susiê (Universidade do Vale do Rio dos Sinos, 2021)
In order to attend the needs and demands of the citie’s population, it has undergone countless transformations over time. In general, these changes have altered the urban dynamics and the quality of life of each cities population, mainly taking into account the significant increase in population density and urban structure since the 19th century. All these changes led, in an attempt to mitigate the impacts that would be caused by the urban fabric’s spread, the zoning’s creation and the search for the separation of uses in each area of the city. This segregation of urban activities still causes conflicts to the urban development of a county and even though the use’s complexity, cities that are compact, dense and sustainable have been debated for some time, the urban activities importance in this debate makes this topic one of the focal issues to be further explored. This research seeks to present, through a decision and permission’s support tool and prohibition of urban activities in Brazilian’s counties, another way of using activities as a parameter for these decisions. Each group of activities has it’ss own characteristics, especially those of medium and large size, as well as each urban area that develops faster than it is possible to update legislation, so, using this information, considering the current reality of each area, can be a way of minimizing conflicts caused by legislation that is often reactive and created with the greatest intention of rsolving existing situations but not proactively planning. The results from the analysis of the tool’s application, that use the Gramado county as a case study, shows that it is possible to use urban activities as a parameter of urban planning in a deeply way and to use the current reality of each urban area as a way of speeding up the approval and the analysis processes within brazilian countie’s city halls, in addition to assisting in decision-making on the permits and prohibitions of activities in each area of the city.
Keywords: Atividades urbanas; Planejamento urbano; Uso e ocupação do solo; Urban activities; Urban planning; Land’s use and occupation.; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo